Telaah Kritis atas Kedudukan Hukum Penasehat Hukum dalam Pembuktian pada Perkara Perdata - Adiman Adiman; Sidi Ahyar Wiraguna (JURNAL ILMIAH NUSANTARA, 2026)
Legal counsel plays a strategic role in evidentiary processes within civil litigation, despite the lack of explicit statutory recognition in Indonesian civil procedural law. This study critically examines the role and authority of legal counsel in constructing evidentiary instruments during court proceedings and evaluates the legal implications of their involvement on procedural and substantive justice. Employing a normative-juridical approach through analysis of legislation, court decisions, and contemporary legal literature, this research reveals that although the Dutch Reglement op de Burgerlijke Rechtsvordering (Rv) and Herziene Inlandsch Reglement (HIR) do not detail the evidentiary role of legal counsel, judicial practice consistently positions them as pivotal actors in submitting, structuring, and interpreting evidence. Findings indicate a norm-practice gap that may generate legal uncertainty, particularly regarding ethical responsibilities and the limits of legal counsel’s authority. Therefore, normative clarification or practical guidelines are urgently needed to define the legal standing of counsel in civil evidentiary processes, thereby reinforcing principles of fairness, predictability, and accountability in civil litigation.